Differential Subordination Properties for Non-Bazilevič Functions Connected with a q-Calculus Operator - Ali, Ekram E.; Oros, Georgia Irina; El-Ashwah, Rabha M.; Kota, Wafaa Y.; Albalahi, Abeer M. (Contemporary Mathematics, 2025)
This paper demonstrates applications of q-calculus operators in geometric function theory with the use of differential subordination properties on non-Bazilevič functions with respect to k-symmetric in this study. The method of the differential subordination theory is applied in developing subordination results involving the new class of univalent functions introduced and studied in the work. Several geometric properties of the class of functions are established in the study. The results generalize many known results in literature. Such previously proved results are presented as corollaries. Different examples are also provided based on the results.